2011
DOI: 10.1002/adhm.201100013
|View full text |Cite
|
Sign up to set email alerts
|

Magnetic Nanocomposite Sol–Gel Systems for Remote Controlled Drug Release

Abstract: The remote heating of iron oxide nanoparticles in an alternating magnetic field is used to drive a thermoresponsive sol-gel block copolymer, Pluronic® F-127, through the upper phase transition temperature. This phase change triggers an accelerated release rate of a model drug. Actuation and return to baseline levels are demonstrated for multiple AMF doses.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
20
0

Year Published

2012
2012
2021
2021

Publication Types

Select...
7
1

Relationship

2
6

Authors

Journals

citations
Cited by 23 publications
(20 citation statements)
references
References 37 publications
0
20
0
Order By: Relevance
“…58 The nanocomposite sol-gel can be easily injected percutaneously into a patient where the system will automatically gel upon reaching physiological temperatures (Fig. 8(A)).…”
Section: Application Of Nanocomposite Hydrogelsmentioning
confidence: 99%
“…58 The nanocomposite sol-gel can be easily injected percutaneously into a patient where the system will automatically gel upon reaching physiological temperatures (Fig. 8(A)).…”
Section: Application Of Nanocomposite Hydrogelsmentioning
confidence: 99%
“…For example, thermoresponsive magnetic hydrogels were developed by Campbell et al who showed a fourfold enhancement of drug release. Other magnetic thermoresponsive nanocomposites based on the combination of certain polymers, nanogels, or lipids, together with iron oxide NPs, were developed in which therapeutic compounds (or drug models), such as lysozyme, sodium fluorescein, ibuprofen (IBU), and nifedepin, were released by the triggered thermal effect of a remote AMF ( Figure ) …”
Section: Representative Biomedical Applicationsmentioning
confidence: 99%
“…Researchers have applied the remote heating capability of MNPs to trigger various thermal transitions in macroscale materials or systems [46–63], and in the following, we highlight a few recent examples of novel materials and systems where AMF triggered thermal transitions resulted in modulated release of a drug. In one strategy, Campbell et al developed nanocomposite systems designed to be in situ-gelling and thus injectable [48, 49].…”
Section: Remote Controlled Drug Therapymentioning
confidence: 99%
“…In another example of a thermoresponsive injectable systems, Hawkins et al developed a nanocomposite sol-gel system based on Pluronic ® F-127 and iron oxide MNPs [46]. When exposed to an AMF (296 kHz, 27.9 kA/m), it was demonstrated that pulsatile release of lysozyme could be achieved, although only over short time frames for the system composition studied.…”
Section: Remote Controlled Drug Therapymentioning
confidence: 99%